Understanding Financial and Access Factors in Housing Decisions: An Economic Education Perspective from Phnom Penh - Ou, Berna; Narith, Por; Pio, Sario T (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to examine the relationship between Financial and Access Factors such as price, financing, personal economic conditions, public services and social stability and consumer purchase intention in Phnom Penh’s residential real estate market. Methodology: In this study, a quantitative survey method was conducted employing structured questionnaires via Google Forms. The date was analyzed with IBM SPSS Statistics 27, using descriptive statistics, Pearson correlation and reliability testing (Cronbach’s Alpha). Content validity was assessed via the Content Validity Index after expert review. Main Findings: The study found a significant positive relationship between Financial and Access Factors and purchase intention. Personal economic conditions (M = 4.06) and social stability (M = 4.04) scored highest, while price (r = .39), finance (r = .37), public services (r = .41), and social stability (r = .34) showed moderate correlations. The over-all correlation between financial and access factors and purchase intention was r=.42 (p <.001). Novelty/Originality of this study: This study is the only research that integrates multiple Financial and Access Factors in terms of price, finance, personal economic conditions, public services, and social stability into one model of purchase intention in Phnom Penh real estate market. By focusing on the context of an emerging economy, it contributes to current understanding and provides fresh insights to the relevant stakeholders including policy makers, developers, and consumer behaviour and housing affordability scholars. It also contributes to economic education by illustrating how financial literacy and access awareness shape consumer decision-making and can guide educational and policy initiatives for sustainable social development.